Some data about the milk and meat production traits of buffalo (Bubalus bubalis) - Barna, Brigitta; Csapó, János; Holló, Gabriella (Acta Agraria Kaposváriensis, 2012)
In this study the milk and meat production traits of Hungarian buffalo population was examined and the findings were corresponded to the results of foreign buffalo researches and cattle. The examined buffalo milk samples (n=10) had higher content of dry matter (17.4%) and fat (7.33%), than cow milk, besides this the buffalo milk is richer in protein (4.19%). The milk of buffalo is very good for cheese making, because the proportion of casein fraction (79.4) is high inside the whole protein content. The examined meat production traits of examined buffalo heifers (n=12) were lower than that of cattle. The dressing percentage (54.7%), the lean meat content (68%) and the proportion of tendon (1%) were lower, but the content of bone (21%) and fat (10%) were higher in buffalo carcass. Contrary to cattle, the buffalo meat had more dry matter, protein and fat proportion. Higher saturated fatty acids content, however low n-6/n-3 fatty acid ratio characterised the buffalo meat.
Keywords: buffalo; meat production; milk composition